AN ANALYSIS OF THE ABILITY OF THE FIRST YEAR STUDENTS OF SMP IT AZIZIYYAH PEKANBARU IN WRITING DERCRIPTIVE TEXTS - Roza, Resmi; Azhar, Fadly; Erni, Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research was aimed to find out the ability level of the first year students of SMP IT Aziziyyah Pekanbaru in writing descriptive texts. The data were collected in February. The population of this research is the first year students of SMP IT Aziziyyah Pekanbaru. The number of sample 31 students who are chosen by using cluster random sampling technique. This research is a descriptive research where the researcher explained the result of research by describing the data gained .The data are collected using a writing test in form of a picture, that was a picture animal. The result of the data analysis showed that the mean score of the studentsâ ability in writing descriptive text is 61.29. It can be that the ability of the first year students of SMP IT Aziziyyah Pekanbaru in writing descriptive texts is poor. Based on the result of the studentsâ ability in each writing aspect, the lowest score in grammar aspect and the highest score in vocabulary aspectKeywords: Analysis, Writing Ability, Descriptive Text.